Effectiveness of Muscle Energy Techniques in Knee Osteoarthritis Rehabilitation: A Systematic Review - Sulfandy, Sulfandy; Noor Azliyana Azizan; Zarina Zahari; Wahyuni Dwi Cahya (Journal of Liaquat University of Medical & Health Sciences, 2025)
Knee osteoarthritis (OA) poses significant challenges to mobility, pain management, and overall quality of life, particularly in an ageing population. This study aimed to evaluate the effectiveness of MET in treating knee OA by examining the evidence on its effects on joint mobility, pain management, and functional improvement. The following PICO criteria were used to select the studies. Clinical trials that focus on patients over the age of 18, incorporate moderate exercise training, and report outcomes such as knee pain, joint function, or quality of life are included. These trials must be published between 2020 and 2024. Studies with non-specific results, narrative reviews, and meta-analyses are excluded from the analysis. A literature search was conducted using the five databases. The research keywords were determined based on the expertise of the participating authors. After a comprehensive search of multiple databases, 12,105 items were identified, and 12 articles were included in the final review. The results of this systematic review indicate that MET is efficacious in improving function, muscle strength, and flexibility in patients with knee osteoarthritis, thereby enhancing their overall quality of life. Optimizing outcomes for patients with knee osteoarthritis requires the integration of kinesio taping, Proprioceptive Neuromuscular Facilitation (PNF) methods, and structured rehabilitation programs. The use of specific rehabilitation techniques that address both the physical and psychological components of recovery will be crucial for the effective management of knee osteoarthritis as its prevalence increases, particularly among the elderly population.